การพัฒนาการจัดการเรียนรู้แบบ MCIS ต่อมโนมติเรื่อง พันธะเคมี ของนักเรียนชั้นมัธยมศึกษาปีที่ 4 - Bootvisate, Panu; Pathommapas, Nookorn; Muangpatom, Chatchai (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2015)
The Development of Model–Centered Instruction Sequence Learning Management on Chemical Bond Concepts of Matthayomsuksa 4 Students Panu Bootvisate, Nookorn Pathommapas and Chatchai Muangpatom รับบทความ: 27 มิถุนายน 2558; ยอมรับตีพิมพ์: 10 ตุลาคม 2558 บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) เพื่อพัฒนาการจัดการเรียนรู้วิชาเคมีตามแนวทางการจัดการ เรียนรู้แบบ MCIS ของนักเรียนชั้นมัธยมศึกษาปีที่ 4 และ 2) เพื่อเปรียบเทียบมโนมติทางการเรียนวิชาเคมีของนักเรียนชั้นมัธยมศึกษาปีที่ 4 ที่ได้รับการจัดการเรียนรู้แบบ MCIS ก่อนและหลังเรียน การวิจัยนี้ใช้รูปแบบการวิจัยเชิงปฏิบัติการตามแนวคิดของ Kemmis and McTaggart (1988) แบ่งเป็น 3 วงจรปฏิบัติการ แต่ละวงจรปฏิบัติการประกอบด้วยแผนการจัดการเรียนรู้วงจรละ 3 แผน กลุ่มเป้าหมายที่ใช้ในการวิจัยเป็นนักเรียนชั้นมัธยมศึกษาปีที่ 4 ภาคเรียนที่ 2 ปีการศึกษา 2557 โรงเรียนนาดีพิทยาคม อำเภอเฝ้าไร่ จังหวัดหนองคาย จำนวน 22 คน เครื่องมือที่ใช้ในการวิจัยแบ่งออกเป็น 3 ส่วน ประกอบ ด้วย 1) เครื่องมือที่ใช้ในการทดลอง ได้แก่ แผนการจัดการเรียนรู้แบบ MCIS วิชาเคมี เรื่องพันธะเคมี จำนวน 9 แผน 2) เครื่องมือที่ใช้สะท้อนผลปฏิบัติการ ได้แก่ แบบบันทึกหลังการสอนของครู แบบสังเกตพฤติกรรมการจัดการเรียนรู้ ใบงาน/ใบกิจกรรมเสริมการเรียนรู้ แบบสัมภาษณ์นักเรียน และแบบทดสอบท้ายวงจรปฏิบัติ และ 3) เครื่องมือที่ใช้ประเมินผลการวิจัย คือ แบบวัดมโนมติเรื่อง พันธะเคมี วิเคราะห์ข้อมูลเชิงปริมาณโดยการหาค่าเฉลี่ย ร้อยละ วิเคราะห์ข้อมูลเชิงคุณภาพโดยเทคนิคการวิเคราะห์เนื้อหา พบว่า 1) การพัฒนาการจัดการเรียนรู้แบบ MCIS วิชาเคมี เรื่อง พันธะเคมี ประกอบด้วย 9 ขั้นตอน ได้แก่ (1) การมุ่งปรากฏการณ์และตั้งคำถามสำคัญ (2) การสร้างแบบจำลองเบื้องต้น (3) การสำรวจตรวจสอบเชิงประจักษ์ (4) การประเมินและปรับปรุงแบบจำลองเบื้องต้น (5) การแนะนำความคิดทางวิทยาศาสตร์จากสื่อสถานการณ์จำลองและสื่อแอนิเมชัน (6) การประเมินและปรับปรุงแบบจำลอง (7) ประเมินและลงมติแบบจำลองของกลุ่ม (8) ลงมติแบบจำลองของชั้นเรียน และ (9) การใช้แบบจำลองเพื่อทำนายหรืออธิบาย 2) นักเรียนมีคะแนนมโนมติเรื่อง พันธะเคมี ก่อนเรียนเฉลี่ย 27.45 คะแนน (ร้อยละ 45.76) หลังเรียนเฉลี่ย 49.77 คะแนน (ร้อยละ 82.95) ซึ่งมีนักเรียนที่มีคะแนนมโนมติหลังเรียนผ่านเกณฑ์ร้อยละ 70 คิดเป็นร้อยละ 95.45 และมีคะแนนมโนมติเรื่อง พันธะเคมี หลังเรียนสูงกว่าก่อนเรียน คำสำคัญ: มโนมติเรื่องพันธะเคมี การจัดการเรียนรู้แบบ MCIS การวิจัยเชิงปฏิบัติการ Abstract The research purposes of the development of model-centered instruction sequence (MCIS) learning management on chemical bond concepts and achievements of Matthayom suksa 4 students were 1) to develop learning management based on MCIS, and 2) compare students’ chemical bond concepts before and after using the developed MCIS. The study was conducted based on Kemmis and McTaggart’s action research (1998). It consisted of 3 experimental cycles which each cycle consisted of 3 learning plans. The first experimental cycle started from the first lesson to the third one, the second experimental cycle started from the forth lesson to the sixth one, and the third experimental cycle started from the seventh lesson to the ninth one. The research samples were 22 Grade-10 students who were studying in second semester of academic year 2014, Nadeepittayakom School, Phaorai, Nong Khai. The research instruments were 3 parts, i.e., experimental instruments, reflection instruments, and evaluation instruments. Experimental instruments were 9 lesson plans based on MCIS, 3 plans for one experimental cycle. Reflection instruments were teacher journals, classroom observation forms, student tasks, interview forms and cycle progress tests. After the 3 experimental cycles were completed, the conceptual and achievement tests were used to evaluate the study. The quantitative data were analyzed by means and percentage. In addition, content analysis was used for qualitative data. The results found that: 1) The development of MCIS learning management in chemical bond composed of 9 steps, (1) Setting qualified questions from phenomena, (2) Drafting model, (3) Empirical inquiry, (4) Evaluating and modifying the model, (5) Introducing scientific concepts relevant to the phenomena, (6) Reevaluating and modifying the model, (7) Pere assessment, (8) Consensus decision making in the model, and (9) Using mode to address and predict of phenomena; 2) the students’ concepts mean scores in chemical bond before and after using the developed MCIS were 27.45 (45.76%) and 49.77 (82.95%), respectively. The percentage of students who gained the posttest higher than 70 percent of a criterion was 95.45. The posttest mean scores was higher than the pretest mean scores. Keywords: Chemical bond concepts, Model-centered instruction sequence (MCIS) learning management, Action research